2010
DOI: 10.2298/mpns1010601j
|View full text |Cite
|
Sign up to set email alerts
|

Simple in situ decompression for idiopathic cubital tunnel syndrome using minimal skin incision

Abstract: Cubital tunnel syndrome is one of the most frequently occurring compression neuropathy in the upper limb next to carpal tunnel syndrome. Recent minimal invasive technique has prompted us to gain clinical experience with simple in situ decompression with minimal skin incision for idiopathic cubital tunnel syndrome. Sixty six consecutive patients with cubital tunnel syndrome were treated using minimal skin incision technique. The mean age of the patients was 49.7 (range: 15-77) years and average follow up period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…In this study the syndrome was present in 57% of women and affected the left side in 62%. Kamat et al (2014) and Jeon et al (2010) confirmed that the syndrome was more prevalent in women and Kanat et al (2014) confirmed that it involved primarily the upper left limb. Perhaps this is the consequence of women, undertaking jobs previously performed by men.…”
Section: Discussionmentioning
confidence: 62%
“…In this study the syndrome was present in 57% of women and affected the left side in 62%. Kamat et al (2014) and Jeon et al (2010) confirmed that the syndrome was more prevalent in women and Kanat et al (2014) confirmed that it involved primarily the upper left limb. Perhaps this is the consequence of women, undertaking jobs previously performed by men.…”
Section: Discussionmentioning
confidence: 62%
“…A study of 66 patients in 2010 by Jeon et al with 81% of patients with preoperative McGowan stage 1 and 2 having satisfactory outcomes (Me) with a 3% postoperative complication rate of 2 hematomas ( 35 ). Karthik et al demonstrated a CGE of 80% ( n = 46, B) ( 36 ) and Lan et al had a procedural satisfaction rate of 88% with 70% showing symptomatic improvement ( 37 ) (Table 2C ).…”
Section: In Situ Releasementioning
confidence: 99%
“…15 On the basis of the literature's largest systematic review of patient's with ulnar neuropathy (over 2000 patients) following in situ decompression in nonthrowers, both subjective and objective patient-reported clinical outcome measures have illustrated no significant differences in patient satisfaction, pain relief, return to activities (including sports), and scar tenderness versus subcutaneous transposition. 16,17 Unfortunately, the latter lacked any randomized controlled clinical trials and included only 2 prospective cohort studies. Patients with mild or moderate (McGowan Classification grade 1 or 2) ulnar nerve injury have significantly better outcomes than those with severe (McGowan grade 3) injury.…”
Section: Treatmentmentioning
confidence: 99%